THE EFFECT OF PROBLEM-BASED LEARNING AND MOTIVATION ON LEARNING OUTCOMES OF ISLAMIC RELIGIOUS EDUCATION STUDENTS OF SMP NEGERI 1 HELVETIA VILLAGE, LABUHAN DELI DISTRICT DELI SERDANG REGENCY - Abdillah Abdillah; Ridha Anggerita Hutagalung (Universitas Islam Negeri Sumatera Utara Medan, 2019)
The purpose of this study is to find out: (1) The effect of the application ofproblem-based learning models on student learning outcomes of IslamicReligious Education, (2) The influence of student learning motivation onstudent Islamic Education learning outcomes, (3) The effect of theapplication of problem-based learning on students 'Islamic ReligiousEducation learning motivation, (4) The interaction between problem-basedlearning and motivation on students' Islamic Religious Learning outcomes. This research is quantitative research. This study used a quasi-experimental method with a population of 298 students in class VIII ofSMP Negeri 1 Helvetia Village, Labuhan Deli District, Deli SerdangRegency, which consists of 9 groups. Sampling using cluster randomsampling, which consists of 34 students in the experimental class and 35 inthe control class. Data collection instruments are tests and questionnaires.The analysis technique is a two-way ANOVA with 2 X 2 factorial atsignificance α = 0.05 followed by the Scheffe test. The results showed: (1)The application of the problem based learning model to the IslamicReligious Education learning outcomes of students is seen from the valueof the Statistical test fcount 283.31 while the value of ftable 3.96. For dk = 1and the real level α = 0.05. It turned out that the value of fcount 283.31>ftable 3.96 was higher than the average student learning outcomes taughtwith expository learning models. (2) The average high motivation ofstudent learning is based on the results of the statistical test fcount 16.65while the value of ftable 3.96. For dk = 1 and the real level α = 0.05. It turnsout that the value of account 16.65> ftable 3.96 has high learningoutcomes. (3) The average student learning outcomes with PBM caninfluence high student motivation based on the results of statistical testingfcount 283.31 while the value of ftable 3.96. For dk = 1 and the real level α= 0.05. It turned out that the value of account 283.31> ftable 3.96. (4) Theinteraction between learning models and motivation in influencingstudent learning outcomes of Islamic Religious Education based on theresults of statistical testing fcount 3.99 while the value of ftable 3.96.